Perception of Healthcare Providers About the Use of Social Media to Manage a Healthy Diet in Saudi Arabia - Alanzi, Turki; Altuwailib, Maryam; Saadah, Amjad Mohammed; Alanezi, Fahad (Frontiers in Public Health, 2021)
Purpose: The objective of this study is to investigate the perceptions of healthcare providers about the use of social media for healthy diet management in Saudi Arabia. Participants and Methods: A cross-sectional study was designed to investigate the use of social media healthy diet management. The sample constituted 308 healthcare professionals from Saudi Arabia. The social media application, WhatsApp is employed to distribute the questionnaire, which has achieved a response rate of 50.61%. Out of the total participants, 55% of the participants were under 30 years of age, 71% were females, and 55% of the participants had a bachelor's degree. Results: Among the total respondents, 66% used social networking applications more than four hours a day, and 78% utilized social media to get information about a healthy diet. The respondents employed the following platforms for this purpose: Instagram (27%), YouTube (19%), Snapchat (19%), WhatsApp (18%), Twitter (8%), and Facebook (5%). The respondents considered that social media is very helpful to educate (44%), communicate with specialists (33%), and get applications for a healthy diet (38%). They held an opinion that social media is very helpful in improving knowledge about a healthy diet (47%), creating diet awareness (42%), and achieving healthy diet outcomes (37%) and lifestyle (37%). Conclusion: According to the perception of health providers, social media can be used to promote healthy diet management in Saudi Arabia. Also, the growing use of social media in Saudi Arabia represents the potential to create programs that encourage and promote healthy eating habits in the Kingdom of Saudi Arabia. Instagram, YouTube, Snapchat, and WhatsApp platforms can be used for this purpose.